Characteristic elevation of soluble TNF receptor II : I ratio in macrophage activation syndrome with systemic juvenile idiopathic arthritis. (15th September 2017) - Shimizu, M; Inoue, N; Mizuta, M; Nakagishi, Y; Yachie, A
Summary: To investigate the clinical significance of soluble tumour necrosis factor receptor (sTNF-R) II/I ratio as an indicator of the diagnosis of macrophage activation syndrome (MAS) complicating systemic juvenile idiopathic arthritis (s-JIA), we measured the serum sTNF-RI and II levels in 117 patients with s-JIA, including 29 patients with MAS, 15 with Epstein–Barr virus-induced haemophagocytic lymphohistiocytosis (EBV-HLH), 15 with Kawasaki disease (KD) and 28 healthy controls (HCs). We determined their correlation with measurements of disease activity and severity. Furthermore, we measured serum interleukin (IL)-18 levels in patients with EBV-HLH and compared these in levels in patients with MAS. The sTNF-RII/I ratio was elevated significantly in MAS and EBV-HLH patients compared with those in the acute phase of s-JIA and KD patients, whereas there were no significant differences between HCs and those in the acute phase of s-JIA. The sTNF-RII/I ratio increased profoundly as MAS developed and correlated positively with disease activity. Serum IL-18 levels were elevated significantly in MAS patients compared with EBV-HLH patients. The monitoring of serum IL-18 and sTNF-RII/I might be useful for the diagnosis of MAS and the differentiation between MAS and EBV-HLH. Graphical Abstract: